2004
DOI: 10.7205/milmed.169.6.461
|View full text |Cite
|
Sign up to set email alerts
|

Classification of the Severity of U.S. Army and Civilian Reports of Child Maltreatment

Abstract: This study compares reports of the severity of child maltreatment for the U.S. Army and a civilian jurisdiction, Washington State (WS). Such comparisons can provide important information on risk and protective factors in designing prevention programs. An understanding of the differences facilitates the tailoring of interventions to better fit the characteristics of each community. The ages of the children in the WS cases were significantly older than the cases of the Army children. In both populations, neglect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…An alternative hypothesis is that child abuse and neglect are less serious in the army than in the civilian sector of US society and that children are, in fact, not the victims of multiple maltreatments. In a previous paper, we found that differences in the army and the US were largely due to the high rates of neglect found in the US civilian sector (McCarroll et al, 2004b) and more physical abuse was classified as severe in the army (McCarroll et al, 2004a).…”
Section: Discussionmentioning
confidence: 99%
“…An alternative hypothesis is that child abuse and neglect are less serious in the army than in the civilian sector of US society and that children are, in fact, not the victims of multiple maltreatments. In a previous paper, we found that differences in the army and the US were largely due to the high rates of neglect found in the US civilian sector (McCarroll et al, 2004b) and more physical abuse was classified as severe in the army (McCarroll et al, 2004a).…”
Section: Discussionmentioning
confidence: 99%
“…The six studies presented in Table 3 compared child maltreatment in the military and civilian communities (Dubanoski & McIntosh, 1984;Gessner & Runyan, 1995;McCarroll et al, 2004aMcCarroll et al, , 2004bNorth Carolina Child Advocacy Institute, 2004;Raiha & Soma, 1997). Because the aims differed somewhat in each of these studies, the methods used to obtain military and civilian child abuse and neglect data did as well.…”
Section: Comparison Of Child Maltreatment In Military and Civilian Populationsmentioning
confidence: 99%
“…Investigations of additional, nonmilitary-related factors associated with elevated risk of child neglect types are needed to further advance understanding of the etiology of neglect types in both military and civilian families. Despite similarities in how child neglect is defined within military and civilian communities, rates of child neglect are higher in civilian compared to military families (McCarroll, Ursano, Fan, & Newby, 2004a, 2004b; Raiha & Soma, 1997) perhaps due to demographic and economic differences in the populations. For example, the Department of Defense (DOD) Family Advocacy Program (FAP) specifies that neglect entails “negligent treatment of a child through acts or omissions by an individual responsible for the child’s welfare under circumstances indicating the child’s welfare is harmed or threatened” (DOD Manual for Child Maltreatment and Domestic Abuse Incident Reporting System, 2005).…”
mentioning
confidence: 99%